The first record of Gyrodactylus decorus Malmberg, 1957 (Monogenea: Gyrodactylidae) on Alburnus mossulensis in Iraq - Abdullah, Younis S. (Sulaimani Journal for Pure and Applied Sciences, 2021)
The monogeneans Gyrodactylus decorus Malmberg, 1957 (Monogenea: Gyrodactylidae) is recorded and described in the current study for the first time in Iraq on the skin, fins, and gill filaments of five Leuciscidae fish Alburnus mossulensis Heckel, 1843. Out of 56 fish samples randomly collected from the Aw-e Shiler in Sharbazher Region, north of Sulaimani Province in Kurdistan Region-Iraq. Overall, 59 gyrodactylid species are to be recorded from Iraqi fishes. Description and detailed measurements of the parasite mentioned above and photomicrograph of them are studies.
Keywords: Gyrodactylidea; Gyrodactylus decorus; Alburnus mossulensis; Aw-e Shiler